2020
DOI: 10.3390/cells9020311
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aggrephagy for the Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases in older individuals with specific neuropsychiatric symptoms. It is a proteinopathy, pathologically characterized by the presence of misfolded protein (Aβ and Tau) aggregates in the brain, causing progressive dementia. Increasing studies have provided evidence that the defect in protein-degrading systems, especially the autophagy-lysosome pathway (ALP), plays an important role in the pathogenesis of AD. Recent studies have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 185 publications
(214 reference statements)
1
26
0
Order By: Relevance
“…The abnormal autophagosomes accumulation was also recently described in the distal region of axons in neurons of AD patients and animal models, and it was correlated with the impairment of retrograde transport along the axons and with changes in the autophagic clearance of the Aβ peptide [179]. This work is an example of many others showing the autophagy deficit in the "neuronal housekeeper" function by which lysosomes lose the capability to degrade aberrant proteins, thereby participating in the accumulation Aβ peptide and Tau [185][186][187][188][189][190][191][192][193].…”
Section: Lysosomes Dysfunction and Adsupporting
confidence: 67%
“…The abnormal autophagosomes accumulation was also recently described in the distal region of axons in neurons of AD patients and animal models, and it was correlated with the impairment of retrograde transport along the axons and with changes in the autophagic clearance of the Aβ peptide [179]. This work is an example of many others showing the autophagy deficit in the "neuronal housekeeper" function by which lysosomes lose the capability to degrade aberrant proteins, thereby participating in the accumulation Aβ peptide and Tau [185][186][187][188][189][190][191][192][193].…”
Section: Lysosomes Dysfunction and Adsupporting
confidence: 67%
“…APP cleavage products that are present in MVBs can be targeted to the autophagic pathway through the generation of amphisomes [99]. The cytotoxic accumulation and aggregation of Aβ in endolysomes can also permeabilize the lysosomal membrane and lead to the release of Aβ in the cytosol (Figure 2, AD condition) and hence the subsequent clearance is likely to require aggrephagy [111]. Finally, lysophagy that allows the clearance of damaged lysosomes [112] would be of prime importance during AD to prevent the accumulation of damaged lysosomes (Figure 2, AD condition).…”
Section: Relevance Of Autophagy In Amyloid-associated Endosomal Dynamicsmentioning
confidence: 99%
“…There are three protein quality systems have been found to degrade misfolded or aggregated protein, such as ubiquitinated proteasomal degradation, chaperone-mediated degradation, and selective autophagy or aggrephagy [3]. Previous studies have been demonstrated that an increasing trend in the number of AD-related proteins are associated with aggresome [4], and non-pathological proteins could form invasive inclusion bodies as well. It has been found that silencing the expression of ubiquitin ligase HRD1 in SH-SY5Y human neuroblastoma cells prevents the formation of APP [5], and ubiquitin 1 linked to AD is known to regulate presenilin-1, which plays a key role of invasiveness in AD pathogenesis [6].…”
Section: Introductionmentioning
confidence: 99%